Juvenile Myasthenia Gravis: Recommendations for Diagnostic Approaches and Treatment - Della Marina, Adela; Trippe, Heike; Lutz, Soeren; Schara, Ulrike (Neuropediatrics, 2014)
Juvenile myasthenia gravis (JMG) is an autoimmune disorder of neuromuscular transmission caused by production of antibodies against components of the postsynaptic membrane of the neuromuscular junction. Ethnicity has influence on incidence, clinical presentation, and the course of the disease. The patients present with a wide range of symptoms–from isolated intermittent ocular symptoms to general muscle weakness with or without respiratory insufficiency. Compared with adults and adolescents, the clinical signs and course of disease in children exhibit differences and occasionally untypical symptoms. Therefore, JMG is often missed and the diagnosis delayed. Isolated ocular symptoms are frequent at onset, spontaneous remission or intermittent symptoms over the longer period of time can occur. Very young children may present with generalized muscle weakness already during the second year of life and in this patient group, specific antibodies can only be slightly increased or even negative. Existing therapeutic options include immunosuppressive therapy and thymectomy but potential long-term side effects on the growing organism and possible influence on immune response in very young children should be considered. Specific clinical symptoms, diagnostic procedures, and a therapeutic approach with consideration of this age group's specificities are discussed.
Keywords: juvenile myasthenia gravis; clinical symptoms; differential diagnosis; diagnostic workup; therapy